2015
DOI: 10.1002/jbm.a.35407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microgrooved surface topography on osteoblast maturation and protein adsorption

Abstract: Microgrooved surfaces have been used extensively to influence cell contact guidance. Guiding cell growth, extracellular matrix deposition, and mineralization is important for bone implant longevity. In this study, we investigated the osteoblast response to microgrooved metallic surfaces in serum-supplemented medium. Groove spacing was comparable with the spread osteoblast size. Focal adhesions were observed to confine to the intervening ridge/groove boundaries. Osteoblasts bridged over the grooves and were una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…The synergistic enhancement of cell guidance by superimposed physical and chemical cues has been reported by a number of studies based on nonspatial deposition of the bioactive substrates over micropatterns, the spatial localization and covalent bonding, or microcontact printing (µCP) of bioactive molecules over preformed micropatterns on hard surfaces, or induction of tubulogenesis by the systems prepared as 2D covalent immobilization of bioactive molecules on hydrogels . In that respect, microfabrication techniques, such as photolithography present opportunities for spatial arrangement of physical and biochemical cues with micron‐scale precision …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The synergistic enhancement of cell guidance by superimposed physical and chemical cues has been reported by a number of studies based on nonspatial deposition of the bioactive substrates over micropatterns, the spatial localization and covalent bonding, or microcontact printing (µCP) of bioactive molecules over preformed micropatterns on hard surfaces, or induction of tubulogenesis by the systems prepared as 2D covalent immobilization of bioactive molecules on hydrogels . In that respect, microfabrication techniques, such as photolithography present opportunities for spatial arrangement of physical and biochemical cues with micron‐scale precision …”
Section: Introductionmentioning
confidence: 96%
“…19 In that respect, microfabrication techniques, such as photolithography present opportunities for spatial arrangement of physical and biochemical cues with micron-scale precision. 20,21 In this study, we aimed to prepare a 3D bilayer construct as a Bruch's membrane and the choroid of retina which can be used as a model for retinal diseases and might have a potential for use in the repair of retinal degenerations. RPE cells were cultured as a monolayer on a highly permeable and mechanically strong electrospun silk fibroin (ESF) mat to mimic Bruch's membrane.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ko et al reported that a hydrophilic surface could strengthen the binding of adhesion proteins to the surface. De et al reported that fibronectin in medium selectively adsorbs onto the ridge/groove boundaries of microgrooved metallic surfaces. In this study, DMLS surface was found to be more hydrophilic, and its hierarchical micro/nanoscale topography exhibited greater protein adsorption ability than the SLA and Ti surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…In general, substrates with nanoscale topographical features have been found to assist cell attachment (Bacakova et al, 2011). Due to the large variety of surfaces studied so far, identifying general trends in how cells react to topographical cues is a difficult endeavor (De Luca et al, 2015). For example, random nanotopographical patterning may either promote or inhibit cell-matrix adhesion depending on cell type, pattern type, and other parameters such as surface chemistry or substrate elasticity (Cha et al, 2013;Dalby et al, 2007Dalby et al, , 2014.…”
Section: Surface Topographymentioning
confidence: 99%
“…Protein coatings, such as Type I collagen (Chuah et al, 2015;Kuddannaya et al, 2013) or fibronectin (Kuddannaya et al, 2013;Wang et al, 2012e;Yamada et al, 2014), can be applied to facilitate attachment of MSCs and iPSCs to hydrophobic surfaces like polydimethylsiloxane (PDMS). Different surface properties provided by these modifications can affect the density and configuration of protein adsorption prior to cell culture or from media, which in turn affects cell adhesion and growth (De Luca et al, 2015). In addition to supporting cell attachment, immobilized ligands may be used to influence cell signaling.…”
Section: Surface-immobilized Biosignalsmentioning
confidence: 99%